Electron Energy Enhancement by Comparison of Linearly and Circularly Polarized Laser Pulse in Vacuum Using Different Values of Magnetic Fields - Singh, Ravindra (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
Energy enhancement by a comparison of circularly and linearly polarized laser pulse during acceleration of the electrons by a Gaussian laser pulses has been investigated. On comparison these two it is found that for the linearly polarized laser pulse the y-coordinate has a finite value and approximately zero for a circularly polarized laser pulse. It is noticed that there is a advantage of circularly polarized field. The comparison is done at high values of the magnetic field. The variation of electron energy with laser spot size, laser intensity, initial electron energy and initial phase has been studied. The maximum energy of the electrons gets enhanced for a circularly polarized in comparison to a linearly polarized laser pulse due to axial symmetry of the circularly polarized pulse. The ycomponent of the electric field of circularly polarized laser pulse contributes to the higher energy gained by the electrons.